Research on spatial prediction technology for mitigating tunnel inrush disasters under complex geological conditions in China’s Hengduan Mountain Range - Yang Zou; XiuJun Dong; Tao Feng; ZhengXuan Xu; Hailin He; ZhangLei Wu (Scientific Reports)
Abstract The proportion of railway high-altitude buried tunnels in complex and dangerous mountainous areas in southwest China is exceptionally high. With the characteristics of suddenness, intermittency, instantaneousness, and destruction, inrushinrushing and collapse is one of the main risks in the tunnel construction process. Therefore, in the design and construction process of tunnels in Hengduan Mountain area, it is very important to identify the mechanism of sudden s inrushing and collapse risks, predict the spatial location and scale of possible inrushing and collapse, and formulate corresponding tunnel design and construction response measures. In order to achieve the above goals, through extensive exploratory attempts and experiments, it has been found that the use of multi-source information during the survey period can analyze the sources and channels of tunnel water inrushing, as well as the mechanism of water inrushing disasters; By utilizing high-definition images of the excavation surface, ultra deep directional drilling information data, and geophysical 3D attribute information data obtained during tunnel excavation, modeling, coordinate conversion, and 3D integration can be carried out. Various information can be compared and verified with each other, and spatial prediction of potential inrushing and collapse risks in front of the excavation surface can be made, and ultimately response measures for potential or existing surge disasters can be determined. This spatial prediction and analysis method is highly effective and has practical and promotional value.